WATAK TOKOH PROTAGONIS DALAM NOVEL GURU AINI KARYA ANDREA HIRATA - Abdoel Gafar; Kiki Sari (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aims to describe the protagonist character in the novel Guru Aini by Andrea Hirata. The protagonist Desi Istiqomah has eight aspects: honest, clever, clever, humble, loyal, generous, defender, and independent. This research is qualitative descriptive research. Qualitative descriptive research is intended to investigate circumstances, conditions or other things, the results presented in the form of research reports in the form of data. The data in this research is in the form of quotations in the novel Guru Aini by Andrea Hirata. This research shows that there is the character of Desi Istiqomah in the novel Guru Aini by Andrea Hirata. Based on the results of this research, it can be concluded that the protagonist of the character Desi Istiqomah in the novel Guru Aini by Andrea Hirata found eight aspects. The most dominant element is the intelligent character of seventeen quotations. While the most minor element is loyal at two quotes. Keywords: analysis, character, protagonist, novel